Reservoir Simulation Model Using Water Injection and Water Alternating Gas Injection Techniques in KEYI Oilfield, Moglud Basin, Sudan - Fatima Musa Edris; Liu Yue Tian (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2022)
Simulation is only way to describe quantitatively the flow of multiple phases in a heterogeneous reservoir. Construction of reservoir simulation model requires a lot of data such as the types of rock and fluid properties. Enhancing the recovery of an oil reservoir is one of the major roles of any oil company. This is achieved by development of the oilfields by employing different techniques such as infill drilling, water injection, gas injection, water alternate gas (WAG) injection and even thermal methods. Reservoir simulation studies using water injection and water alternate gas injection for KEYI oil field, Muglad Basin, Sudan. The purpose of this simulation study is to determine the suitable method for increase and enhanced oil recovery. The simulation model was developed using two-phase, 3D and black oil options in ECLIPSE soft ware. Finally, the simulation result showed that water alternating gas technique is the best method to improve oil recovery from KEYI oil field, Muglad Basin, Sudan.